Efficacy of Shadow-Based Needle Positioning System in Performing CT Image-Guided Percutaneous Biopsy of Lung Lesions: Our Initial Experience - Keshava, Shyamkumar N.; Moses, Vinu; Padmanabhan, Aswin (Indian Journal of Radiology and Imaging, 2022)
Context Computerized tomography (CT) is widely used for various interventions and there is a need for an effective navigation tool, for best outcomes.Aim The study was performed to evaluate the efficacy of light- and shadow-based needle positioning assistance device, an innovative navigation tool over the conventional freehand technique, in performing CT image-guided percutaneous interventions.Settings and Design This randomized control trial was performed among patients undergoing CT-guided percutaneous intervention for lung pathologies.Methodology A total of 60 participants were randomized into an intervention group and a control group. The accuracy of needle insertion and other efficacy parameters were assessed for both groups. Post needle placement, CT images were used to evaluate the study endpoints.Statistical Analysis Statistical analysis was performed using SPSS ver. 20 software.Results The mean needle positioning accuracy was 2.1 mm in the experimental group compared with 7.2 mm in the control group freehand procedures. The average time to position the needle at the desired target location was 2.5 minutes in the assisted procedure as compared with 5.3 minutes in the freehand procedure (p < 0.05). The total number of check scans required to position the needle was 1.3 for assisted procedures and 1.9 for freehand procedures.Conclusion The use of shadow-based assistance device for CT-guided interventions is proven to be efficient and safer with high needle positioning accuracy.
Keywords: biopsy; CT-guided intervention; lung; radiation exposure